2009
DOI: 10.1007/s10533-009-9333-9
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variation of DOC concentration and annual loss of DOC from an Atlantic blanket bog in South Western Ireland

Abstract: This paper represents the first continuous dissolved organic carbon (DOC) record, measured in a stream draining an Atlantic blanket bog in South West Ireland for the calendar year 2007. At 30-min intervals, the DOC concentration was automatically measured using an in-stream spectroanalyser whose variation compared well with laboratory analysed samples taken by a 24-bottle auto-sampler. The concentration of DOC ranged from 2.7 to 11.5 mg L -1 with higher values during the summer and lower values during the wint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
70
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(88 citation statements)
references
References 41 publications
15
70
3
Order By: Relevance
“…The estimated export of the two carbon fractions for 2010, 9.5 t C km 2 year -1 for DOC and 6.2 t C km 2 year -1 for POC, are within the range reported in other studies from peatland catchments (Naden et al, 2010;Koehler et al, 2009;Agren et al, 2007;Clark et al, 2007;May et al, 2005;Worrall et al, 2003;Hope et al, 1997). On an annual basis, the POC load was estimated to represent just under 40 % of the combined POC and DOC load.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The estimated export of the two carbon fractions for 2010, 9.5 t C km 2 year -1 for DOC and 6.2 t C km 2 year -1 for POC, are within the range reported in other studies from peatland catchments (Naden et al, 2010;Koehler et al, 2009;Agren et al, 2007;Clark et al, 2007;May et al, 2005;Worrall et al, 2003;Hope et al, 1997). On an annual basis, the POC load was estimated to represent just under 40 % of the combined POC and DOC load.…”
Section: Discussionsupporting
confidence: 84%
“…Carbon is exported in a number of different forms from these systems, including as dissolved inorganic carbon (DIC), dissolved organic carbon (DOC) and particulate organic carbon (POC) in catchment streams, and as gaseous emissions of carbon dioxide (CO 2 ) and methane (CH 4 ) from soil carbon stores (Dinsmore et al, 2011). Published estimates of DOC export range from 1.5 t C km 2 year -1 to 14.2 t C km 2 year -1 (Koehler et al, 2009;Clark et al, 2007;Worrall et al, 2003;Hope et al, 1997) while estimates of POC export range from 0.1 t C km 2 year -1 to 31.7 t C km 2 year -1 (May et al, 2005;Worrell et al, 2003;Hope et al, 1997). Despite the potential for these two carbon sources to contribute to greenhouse gas emissions when mineralised (Davidson and Janssens, 2006), DOC and POC export from peat stores are often ignored in catchment studies, and are generally not included in national greenhouse gas emissions budgets (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…For example the driest year of the study period, 2013, displayed the minimum yield. The estimated annual yields reported here are broadly in line with the 9.5 t C km 2 yr -1 and 13.7 t C km 2 yr -1 estimated DOC export from the Glenamong sub-catchment in 2010 and 2011 10 respectively (Ryder et al 2014) and broadly within the ranges reported in other studies from peatland catchments (Naden et al 2010;Koehler et al 2009;Clark et al 2007) …”
Section: Carbon Export From the Sub-catchmentssupporting
confidence: 90%
“…This equates to a fluvial TOC flux per unit area over the whole catchment (5200 km 2 ) of 88 g C m −2 yr −1 , a figure which far exceeds those reported for northern peatlands (10-30 g C m −2 yr −1 ; Billet et al, 2010;Koehler et al, 2009;Nilsson et al, 2008). The entire land area of Indonesia is ∼1.9 × 10 6 km 2 of which over 10% (206 950 km 2 ) is covered by peat soils (Page et al, 2010).…”
Section: Dry Season Vs Wet Seasonmentioning
confidence: 84%